Pendidikan Jiwa dalam Perspektif Syaikh Ibn Qayyim al-Jauziyyah - Achmad Tamyiz; Siti Rokhimah (TSAQOFAH, 2026)
Although education of the soul is an important aspect of Islamic education, studies on the concept of education of the soul according to Ibn Qayyim al-Jauziyyah and its relevance to the development of Muslim character in the modern era still need to be strengthened. This study aims to examine the concept of education of the soul according to Ibn Qayyim al-Jauziyyah and explain its relevance to Islamic education. This study used a library research method by analyzing various works of Ibn Qayyim, such as Madarij al-Salikin, Ighatsat al-Lahfan, and Zad al-Ma’ad, as well as other relevant supporting literature. The results of the review show that education of the soul according to Ibn Qayyim focuses on the process of purifying the heart from various spiritual diseases, controlling desires, strengthening faith, and habituating worship and noble character. Ibn Qayyim divides the condition of the human soul into three levels, namely nafs al-ammarah, nafs al-lawwamah, and nafs al-mutma’innah. Education of the soul is carried out through various methods, such as repentance, remembrance of Allah, self-reflection, patience, sincerity, and following the guidance of the Messenger of Allah (peace be upon him). These findings confirm that Ibn Qayyim’s concept of education of the soul has strong relevance to Islamic education because it emphasizes the formation of human beings who are faithful, morally noble, and balanced between spiritual and material needs. The implications of this study contribute to the development of Islamic education based on tazkiyatun nafs as a strategy for character development and the strengthening of Islamic values in facing moral and spiritual crises in the modern era.